Optimizing Prenuptial Agreements for Asset Protection: A Maqashid Sharia Based Approach - Rohmadi, Rohmadi; Faizin, Muadil; Zain, R. Dedy Chairil; Nasution, Yenni Samri Juliati; Suhardiman, Suhardiman (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This research aims to explore the optimization of PNAs for asset protection by integrating the principles of maqashid sharia, which emphasize the protection of religion, life, intellect, progeny, and wealth. The high divorce rates in Indonesia, mainly due to online gambling, highlight the vulnerability of asset protection at the beginning of marriage and underscore the importance of prenuptial agreements (PNAs). This research uses a qualitative approach with normative juridical analysis methods. Secondary data was obtained through critical analysis of related literature, including the Indonesian Marriage Law, previous academic studies, and other legal documents related to the PNA. The descriptive-analytical method is used to evaluate the effectiveness of PNA in protecting assets based on maqasid sharia principles. The main question addressed is how PNAs can be effectively utilized to safeguard personal assets and reduce conflicts within marriage. This study critically analyzes Law No. 16/2019 Indonesian Marriage Law and suggests improvements to enhance the effectiveness of PNAs. The analysis reveals that detailed provisions on the content of PNAs, simplification of the legalization process, mandatory legal consultation, and enhanced public education are essential for optimizing asset protection. The findings underscore the necessity of PNAs in providing legal certainty, promoting justice, and ensuring the welfare of both parties in marriage, aligning with the maqashid sharia principles. This research contributes to the existing literature by offering a new perspective on applying Maqashid sharia in PNAs and provides practical guidelines for drafting effective and Sharia-compliant PNAs.